2007
DOI: 10.1523/jneurosci.4583-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Loss of Dopaminergic Neurons in the Ventral Midbrain of Adult Mice Heterozygote forEngrailed1

Abstract: Engrailed1 and Engrailed2 (En1 and En2) are two developmental genes of the homeogene family expressed in the developing midbrain. En1 and, to a lesser degree, En2 also are expressed in the adult substantia nigra (SN) and ventral tegmental area (VTA), two dopaminergic (DA) nuclei of the ventral midbrain. In an effort to study En1/2 adult functions, we have analyzed the phenotype of mice lacking one En1 allele in an En2 wild-type context. We show that in this mutant the number of DA neurons decreases slowly betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
208
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(229 citation statements)
references
References 43 publications
16
208
5
Order By: Relevance
“…Recent studies have proposed a maintenance and survival role for some of the factors studied here (EN1, LMX1B, NURR1 and PITX3), in addition to their known developmental roles [49][50][51][52][53][54][55] (reviewed in [6,15,49]). We therefore analyzed their expression in 30d-differentiated control and Bcl-X L hVMl cells.…”
Section: Long-term Expression Of Transcription Factors Required For Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have proposed a maintenance and survival role for some of the factors studied here (EN1, LMX1B, NURR1 and PITX3), in addition to their known developmental roles [49][50][51][52][53][54][55] (reviewed in [6,15,49]). We therefore analyzed their expression in 30d-differentiated control and Bcl-X L hVMl cells.…”
Section: Long-term Expression Of Transcription Factors Required For Fmentioning
confidence: 99%
“…Bcl-X L effects on maturation are marginal, as discussed later. EN1, LMX1B, NURR1 and PITX3 are not only involved in development, but also in the survival/maintenance of functional A9-DAn ( [50][51][52][53][54] reviewed in [6,15,24,49,77]). In control hVMl cells the expression levels of these genes first increase during differentiation (but for PITX3), to later return to values close to basal levels ( Fig.…”
Section: Maturation Function and Maintenance Of Danmentioning
confidence: 99%
“…The test was performed as previously described (Sonnier et al, 2007). Male C57/bl6 mice (n ¼ 11 per sucrose concentration), placed in individual cages 2 weeks before the test, were submitted to a water vs sucrose two-bottle preference test.…”
Section: Sucrose Preferencementioning
confidence: 99%
“…Recombinant En1 and En2 are internalized by live cells allowing functional access to cytoplasm and nucleus. When infused in the midbrain of En12/þ mice, they provoke a complete arrest of cell death [11]. Thus, En1/2 can be considered a therapeutic protein and this experiment importantly suggests that non-cell-autonomous and cell-autonomous properties of HPs can be shared as the exogenously added protein can substitute for the endogenous one.…”
Section: Engrailed1/2 Influences Mitochondrial Functionmentioning
confidence: 89%
“…In this context, adult En1/2 expression in the ventral midbrain dopaminergic (mDA) nuclei, the Substantia Nigra pars compacta (SNpc) and ventral tegmental area (VTA), which also expresses Otx2, is of great interest. In 2007, it was shown that the loss of one En1 allele (En12/þ mouse) leads to the progressive death of mDA neurons [11]. The neurons start dying at six weeks after birth and death continues progressively until, after 1 year, 40% and 20% mDA neurons are lost in the SNpc and VTA, respectively.…”
Section: Engrailed1/2 Influences Mitochondrial Functionmentioning
confidence: 99%